2014
DOI: 10.1159/000365391
|View full text |Cite
|
Sign up to set email alerts
|

Complete Recovery of a Wide Local Reaction by the Use of Dexrazoxane 72 Hours after Epirubicin Extravasation: Case Report and Review of the Literature

Abstract: Background: Accidental extravasation of anthracyclines might result in devastating side effects and complications, including necrosis of tissue, with impairment of neighboring structures - most of them requiring surgery. Following recent approach guidelines, intravenous administration of dexrazoxane within 6 h after the event is recommended. Case Report: We report on a 63-year-old female patient with breast cancer treated with epirubicin combination therapy. She experienced extravasation on the distal right ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…No improvement was slightly more common than improvement , suggesting that skin injuries caused by epirubicin hydrochloride extravasation may be difficult to treat. On the other hand, several reports have indicated that dexrazoxane treats skin injuries caused by anthracycline (epirubicin hydrochloride) extravasation 13,14. Overall, proper extravasation management may reduce skin injuries caused by epirubicin hydrochloride extravasation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No improvement was slightly more common than improvement , suggesting that skin injuries caused by epirubicin hydrochloride extravasation may be difficult to treat. On the other hand, several reports have indicated that dexrazoxane treats skin injuries caused by anthracycline (epirubicin hydrochloride) extravasation 13,14. Overall, proper extravasation management may reduce skin injuries caused by epirubicin hydrochloride extravasation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several reports have indicated that dexrazoxane treats skin injuries caused by anthracycline (epirubicin hydrochloride) extravasation. 13,14 Overall, proper extravasation management may reduce skin injuries caused by epirubicin hydrochloride extravasation.…”
Section: Epirubicin Hydrochloride (Anticancer Drug)mentioning
confidence: 99%
“…These suggest the best treatment is dictated by the class of chemotherapy agent. For vesicants early localisation with a cold compress every 20 minutes, four times a day for 24-48 hours and treatment ideally within 6 hours with intravenous dexrazoxane and topical Dimethyl sulfoxide [10] . This is reflected in several case reports where the systemic use of dexrazoxane has resulted in favorable outcomes during extravasation injury involving central venous catheters [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Nevertheless, significant clinical improvement has been reported in cases of dexrazoxane being initiated even as late as 72 hours after peripheral extravasation. 17 Dexrazoxane administration can lead to neutropenia, thrombocytopenia and liver enzyme elevation, but these effects were mostly reported with prolonged dexrazoxane use. 11 Dexrazoxane was administered in three cases of intrapleural and mediastinal anthracycline extravasation.…”
Section: Discussionmentioning
confidence: 99%